(untitled) (Research, Society and Development, 2021)
The objective was to identify and describe the scientific evidence of nursing to women in the puerperal period. This is an integrative literature review. The study was carried out through indirect consultation of scientific productions available on the Virtual Health Library (VHL) platform in the following online databases Latin American Literature in Health Sciences (LILACS), Database in Nursing (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE) with a time frame from 2016 to 2021. The descriptors "Nursing Care" were used; "Puerperium"; "Women’s Health". The study had as inclusion criteria: articles in Portuguese, English or Spanish, original articles in full, available and free of charge. Exclusion criteria were established articles that did not meet the research objectives, review studies and abstracts.219 studies were found, after applying the inclusion criteria where 75 articles were selected for reading the abstracts, then 10 articles that met the research objectives were selected to be part of the study. After analysis of the results two categories emerged for discussion of the theme, namely: Postpartum nursing care; The puerperal woman’s perception of nursing care. It is concluded that nursing must be constantly improving for assistance that can meet the other demands and singularities of every puerperal woman, because the puerperium is a phase with the possibility of risks and harm, where care must be aimed at prevention complications in the mother and also in the newborn.